Photoaging and actinic keratosis in Danish outdoor and indoor workers - Grandahl, Kasper (Photodermatol Photoimmunol Photomed, 2019)
BACKGROUND: The risk of photoaging and actinic keratosis caused by work related solar ultraviolet radiation exposure has not previously been investigated in Nordic countries. The objectives of this study were to describe the occurrence of photoaging, actinic keratosis, and keratinocyte cancer in a population of Danish outdoor and indoor workers, and investigate the association between these clinical findings and semi‐objective measures of work related solar ultraviolet radiation exposure in the same population. METHODS: A clinical cross‐sectional study of the occurrence of facial wrinkles, actinic keratosis, keratinocyte cancer, and melanocytic nevi in a population of Danish outdoor and indoor workers and associations with semi‐objective measures of work related solar ultraviolet radiation exposure based on a combination of dosimetry and self‐report. RESULTS: Work related solar ultraviolet radiation exposure was significantly positively associated with occurrence of facial wrinkles (α = 0.05). Actinic keratosis was associated to status as outdoor worker (OR = 4.272, CI [1.045‐17.471]) and age (P < 0.001, CI [1.077‐1.262]) and twice as common in outdoor workers (10.3% CI [0.05, 0.15]) compared to indoor workers (5.1% CI [0.00, 0.10]). Only two cases of keratinocyte cancer were diagnosed (<1%). Older age was negatively associated with occurrence of melanocytic nevi. CONCLUSION: Outdoor work in Denmark is associated with increased occurrence of facial wrinkles and actinic keratosis from solar ultraviolet radiation exposure, thus justifying sun safety at Danish workplaces from a clinical perspective.